Cultic Calendar and Psychology of Time: Elements of Common Semantics in Explanatory and Astrological Texts of Ancient Mesopotamia - Emelianov, Vladimir (Comparative mythology, 2019)
This article compares two groups of texts: Neo-Assyrian menologies (monthly predictions) and zodiacal horoscopes of the Late Babylonian period. Semantic relationships of both with myths and rituals of the Sumerian and Babylonian cultic calendar are established. The data of cuneiform texts are compared with the data of modern psychophysiology and chronopsychology (X. Gonda and her group). It is assumed that the scribes of the Eighth to Fourth centuries BC reported to the circle of healers and astrologers that diseases of people born in different seasons depended on their temperament and the state of their nervous system. Now we can say that for modern man the rational core of Babylonian astrology lies in the fact that the causes of various changes in psychophysical conditions are not ascribed to constellations, but to geoclimatic periods of the year when these constellations appear. The Babylonians believed that the characteristics of physical and mental development of a person born in a particular period of the year coincide with sensations and symptoms that overtake all people at the same time. Whether this hypothesis is right or wrong is a puzzle that modern science has yet to solve.